Shalat Khusyu’ Menurut Tuntunan Syariat - shalat, khusyu, syari’at (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2014)
This article discusses about the nature of khusu’ prayer based on the Islamic syari’at. Most Muslims judge that a khusu’ prayer is something difficult to learn, while Quran states that one of characteristic of fiirdaus eden is a person who can do the khusu’ prayer.Shalat is an obedience which is different from another one. It was assigned to Prophet Muhammad through isra’ andmi’raj. Shalat is vertical contact between a creater and a creature. Also, it is a constraint to design a very good character. Shalat is puprosed to prevent a bad and illegal action. In order to reach the goal, however, a moslem must do shalat in a such khusu’ manner. It is impossible for a moslem to gain the goal of shalat without doing it in akhusu’ manner.On the other side, due to the lack of comprehension on khusu’ prayer, many people conduct a training of khusu’ prayer as if it is based on the sunnah.Naturallay, the meaning of khusu’ prayer has broader scope compared to what clarified in the training it self.